2017
DOI: 10.1007/s11538-017-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Michaelis–Menten Equation in Protein Synthesis: Effects of Mis-Charged Cognate tRNA and Mis-Reading of Codon

Abstract: The sequence of amino acid monomers in the primary structure of a protein is decided by the corresponding sequence of codons (triplets of nucleic acid monomers) on the template messenger RNA (mRNA). The polymerization of a protein, by incorporation of the successive amino acid monomers, is carried out by a molecular machine called ribosome. We develop a stochastic kinetic model that captures the possibilities of mis-reading of mRNA codon and prior mis-charging of a tRNA. By a combination of analytical and nume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Here, V0 is a single vertex corresponding to the unbound enzyme and there are multiple bound enzyme conformations which change or fluctuate along a sequence, from which irreversible transitions can return to the single vertex in V0. Second, they have been used in studies of the ribosome (17)(18)(19), in which the MM formula was found for the average ribosome velocity as a function of aminoacyl tRNA concentration. Here, V0 is a single vertex corresponding to the bare ribosome conformation and tRNA binding gives irreversible outgoing edges from this vertex.…”
Section: Resultsmentioning
confidence: 99%
“…Here, V0 is a single vertex corresponding to the unbound enzyme and there are multiple bound enzyme conformations which change or fluctuate along a sequence, from which irreversible transitions can return to the single vertex in V0. Second, they have been used in studies of the ribosome (17)(18)(19), in which the MM formula was found for the average ribosome velocity as a function of aminoacyl tRNA concentration. Here, V0 is a single vertex corresponding to the bare ribosome conformation and tRNA binding gives irreversible outgoing edges from this vertex.…”
Section: Resultsmentioning
confidence: 99%
“…To each of the directed spanning trees T µ i , we assign a numerical value, A(T µ i ), which is defined as the product of the |V | − 1 = 6 transition rates in the tree, with transitions i → j defined along the orientation (i, j). The steady state probability distributions are then given by (20) with the normalization factor (21). As a result of this construction, all unnormalized steady state probabilitiesP i = M µ=1 A(T µ i ) for the 7state model are a sum of 39 monomials.…”
Section: Step 4: Steady-state Solution In Terms Of Contributions Frommentioning
confidence: 99%
“…Using the decomposition (20) of the stationary probabilities into contributions from the directed spanning trees one obtains the decomposition…”
Section: Appendix B: Graphical Representations Of Transition and Cyclmentioning
confidence: 99%
See 1 more Smart Citation
“…These suppressor mutations result in an error-prone variant of IF2 that has been shown to initiate with non-formylated Met-tRNA fMet , with elongator aa-tRNAs, and with no tRNA at all in vitro and, presumably, in vivo [18,19]. Almost all of the kinetic models of translation that have been reported so far [29][30][31][32][33][34], have mainly focused on the details of the elongation stage of protein synthesis and have represented the initiation stage of protein synthesis using a single effective rate constant. Here, we have developed a kinetic model that focuses exclusively on the multi-step assembly of the canonical, pseudo, and non-canonical 70S ICs during the initiation stage of protein synthesis.…”
Section: Mechanism and Regulation Of Translation Initiationmentioning
confidence: 99%